Life, death and everything in between - Don McCullin - McCullin, Don 1935- (GOST, 2023)
Life, Death and Everything in Between presents key photographs by Don McCullin. The book aims to be neither a retrospective nor definitive publication, but to present a selection of images valued by McCullin with the benefits of both hindsight and wisdom, 0encapsulating his prolific, varied and ongoing career. The book opens with McCullin's documentary photographs made in London in the 1950s, followed by reportage made in conflicts across Europe, Africa, the Middle East and South-East Asia. More recent photographs in the book link the legacy of the Roman Empire in the Mediterranean and the latest, previously unpublished landscapes made near his home in Somerset.
Ausstellungsdaten ermittelt: Palazzo delle Esposizioni, Rome, Italy (10.10.2023-28.01.2024)
Keywords: McCullin, Don -- 1935-; Fotografie; Photojournalism; Photography; Photographie de presse; Photographie; photojournalism (discipline); Ausstellungskatalog -- Palazzo delle Esposizioni -- 10.10.2023-28.01.2024 -- Rom; Bildband